Biocompatible space charge electret material with antibacterial and antiviral effects and manufacturing method thereof

By combining space-charge electret materials with high positive charge density with cationic polymers and textile substrates, contact electrostatic interactions are used to solve the problems of high irritability and inbiologically friendly existing antibacterial and antiviral materials. It achieves efficient and biocompatible antibacterial, antiviral and viral killing effects, and provides excellent filtration and self-disinfection functions.

CN119278302APending Publication Date: 2025-01-07C POLAR TECHNOLOGIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380034692.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-01-31
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing antibacterial, antiviral and bactericidal materials have problems such as high irritation, inorganic friendly and difficult to use for a long time, and traditional metal ion antimicrobial agents are harmful to the environment and human health.

Method used

A space-charge electret material with high positive charge density was developed. Through contact-activating, non-contact electrostatic interaction and interfacial lipophilic synergistic action, cationic polymers are combined with hydrophobic textile substrates to prepare efficient Antibacterial, antiviral, bactericidal and virulent compositions.

Benefits of technology

It achieves efficient, biocompatible, environmentally friendly antibacterial, antiviral and viral anti-viral effects, suitable for direct and long-term wear and contact, without the need for additional chemical agents, and has excellent filtration and self-disinfection functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278302A_ABST
    Figure CN119278302A_ABST
Patent Text Reader

Abstract

The present disclosure relates to antiviral, antibacterial, viral and / or bactericidal space charge electret materials and compositions comprising space charge electret materials; methods of making and using the materials, methods of making and using the compositions, methods of evaluating the efficacy of the compositions, methods of measuring and testing the compositions, and methods of developing, creating and making new space charge electret compositions.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is related to U.S. Provisional Patent Application No. 63 / 203,763 filed on July 30, 2021, the entire contents of which are hereby incorporated herein. This application is also related to U.S. Provisional Patent Application No. 63 / 260,146 filed on August 11, 2021, the entire contents of which are hereby incorporated herein. This application is also related to U.S. Provisional Patent Application No. 63 / 260,692 filed on August 29, 2021, the entire contents of which are hereby incorporated herein. This application is also related to U.S. Provisional Patent Application No. 63 / 268,201 filed on February 18, 2022, the entire contents of which are hereby incorporated herein. This application is also related to U.S. Provisional Patent Application No. 63 / 364,113 filed on May 4, 2022, the entire contents of which are hereby incorporated herein. Technical Field

[0003] The present invention relates to the field of antibacterial, antiviral, bactericidal and virucidal materials and methods, and in particular to a space-charged electret polymer having antibacterial, antiviral, bactericidal and virucidal effects and its use in the preparation of antibacterial, antiviral, bactericidal and virucidal materials. Background Art

[0004] Microorganisms (such as bacteria, viruses and fungi) are ubiquitous in nature and in the global social environment. They are natural decomposers and play various important roles in global ecosystems. Some of them are essential for the life and physiological activities of animals and plants, while some may cause different types of diseases. The development of antibacterial, antiviral, bactericidal and / or virucidal materials is of significant importance in saving lives and protecting people from infection by harmful microorganisms. With the increasingly frequent outbreaks of new deadly viruses (such as Ebola, swine flu, avian flu, the new coronavirus (Covid-19)), and the subsequent emergence of drug-resistant strains (such as methicillin-resistant Staphylococcus aureus or MRSA), it has become urgent to find new disinfection and microbial eradication materials and methods to help in the continued fight against bacteria and viruses. Summary of the invention

[0005] The present disclosure provides an antimicrobial composition having surprisingly effective antibacterial, antiviral, bactericidal and virucidal properties. The composition comprises a space charge electret material coupled to a hydrophobic material. In selected embodiments, the composition has high efficacy, biocompatibility and environmental friendliness.

[0006] The present disclosure also provides a novel method for capturing and killing microorganisms (such as bacteria and viruses) using space charge electret materials, which includes the steps of contact electrification, non-contact electrostatic interaction and interfacial lipophilicity. In some embodiments, interfacial lipophilicity does not refer to simple contact destruction determined by the degree of amphiphilicity and hydrophobicity. Another embodiment provides a method for identifying biocompatible space charge electret materials with effective antibacterial, antiviral, bactericidal and / or virucidal properties based on compatible cationic polymers and textile substrates.

[0007] Positive charge density

[0008] The space charge electret materials of the present disclosure have a high positive surface charge density. The present disclosure demonstrates that space charge electret materials with a higher positive charge density have increased antibacterial, antiviral, bactericidal and virucidal effects, such as Figure 9-15 In some embodiments, the positive charge density of the space charge electret material is 9.59 nC cm -2 .

[0009] Some embodiments provide a composition comprising a positive surface charge density of 2-35 nC cm -2 、Conductivity is less than 6x 10 at a frequency of 80kHz -7 sm -1 space charge electret material; and surface energy less than 50 mN m -1 hydrophobic material.

[0010] The high positive charge density of space charge electret materials plays a key role in capturing and killing microorganisms (such as bacteria and viruses). First, it helps to attract biohazards via non-contact electrostatic interactions with negatively charged proteins and causes an increase in collision rate. Then contact electrification occurs when the drifting negatively charged biohazard collides with the positively charged electret, resulting in a sharp change in electrostatic potential and a sudden increase in electrical stress. Strong electrostatic fields tightly fix biohazards on positively charged surfaces, and the generated non-uniform electrical stress helps the shearing of key viruses or microbial proteins of biohazards. In a preferred embodiment of the present invention, the high positive charge density of space charge electret materials is uniform or substantially uniform over the entire surface area of ​​the material.

[0011] Space Charge Electret Materials

[0012] In some embodiments, the space charge electret material comprises one or more cationic polymers, such as gelatin, chitosan, cationic peptides, cationic cyclodextrins, cationic dextran, cationic cellulose, polyethylene imine, polylysine, polyamidoamine, poly(amino-co-esters) and poly[2-(N,N-dimethylamino)ethyl methacrylate]. Cationic polymers can be natural, semi-synthetic and / or synthetic, and their polymer structures can be linear, branched, hyperbranched and / or dendrimer-like. The position of the cation-bearing group can be in the main chain or in the side chain.

[0013] Cationic polymers are advantageous and useful because they can kill bacteria without releasing any chemicals using their unique cationic molecular structure. Their antimicrobial mode of action is primarily through contact disruption of microbial cell membranes. The degree of antimicrobial activity of cationic polymers is determined by two factors: the degree of amphiphilicity and the degree of hydrophobicity.

[0014] Example materials of textile substrates include, but are not limited to, natural cotton, wool, cellulose, synthetic polyester, nylon and / or blends thereof. The structure of the textile substrate can be knitted, woven, and nonwoven. Some embodiments include blended textiles consisting of both hydrophilic natural fibers and hydrophobic synthetic fibers.

[0015] The space charge electret material of the present disclosure has both high positive charge density and suitable hydrophobicity, and has particularly effective antibacterial, antiviral, bactericidal and virucidal properties. In the close contact process, the hydrophobicity of the space charge electret material helps its lipophilic partition to insert into the cell membrane of microorganisms via van der Waals interactions, thereby contributing to easier and faster destruction of biohazards.

[0016] In some embodiments, the high positive charge density is 9.59 nC cm -2 .like Figure 9-11 and 13, with a high positive charge density (e.g., 9.59 nC cm -2 ) and appropriate wettability (surface energy should be between 20 and 61 mJ m -2 or mN m -1 The space charge electret material (between) has excellent antibacterial, antiviral, bactericidal and virucidal effects against Staphylococcus aureus, SARS-229E, SARS-CoV-2 and Coxsackievirus B6, with an efficacy of more than 98% within 5 minutes.

[0017] Methods for measuring space charge density

[0018] Another embodiment provides a method for identifying compositions having surprisingly effective antimicrobial properties by evaluating the contact charging properties of space charge electret materials by measuring the electrostatic charge of the material. The degree of contact charging is quantitatively evaluated using the positive charge density.

[0019] An exemplary method for measuring the positive charge density of a space charge electret material includes a two-layer setup consisting essentially of a bottom acrylic plate with a 6 cm x 6 cm bonded electrode layer affixed and an upper acrylic plate with a reference material / electrode layer of the same size affixed. A polytetrafluoroethylene (PTFE) membrane is affixed as the reference material.

[0020] Favorable properties

[0021] The presently disclosed compositions have several significant advantages over current methods.

[0022] Current disinfection methods have different drawbacks. Chemical disinfectants and sanitizers often trigger irritation / toxicity to the skin, mucous membranes and respiratory system, and most are bio-unfriendly to humans when used in direct and / or long-term wear / contact situations (e.g., personal protective equipment masks and clothing). In addition, they are also not suitable for air purification systems with long-term disinfection and sterilization effects because their low molecular weight and low surface adhesion cause them to evaporate or sweep easily.

[0023] Metal ions (such as mercury, silver, copper, brass, bronze, tin, iron, lead and bismuth ions) are another class of antimicrobial agents that can kill microorganisms or inhibit the growth of microorganisms based on the microdynamic effect. However, the simple release of these metal ions may also be fatal to humans and harmful to the environment. A less invasive and less toxic method is to dope / incorporate the desired metal ions with other materials (such as polymers) to form nanoparticles, fibers, coatings or films. They are not easily removed by simple cleaning, but because the surface energy of the metal is high, they are usually covered by materials with lower surface energy, resulting in lower antimicrobial effects.

[0024] In contrast, disclosed herein are highly effective, biocompatible, environmentally friendly materials that are able to effectively kill microorganisms and can be used for direct and prolonged wear and contact.

[0025] Textile substrates treated with space charge electret materials are effective in preventing viruses and bacteria from penetrating textile filters. The virus filtration efficacy and bacterial filtration efficacy of cellulose / polyester textiles treated with BPEI space charge electret materials have been demonstrated to exceed 99.9%.

[0026] By controlling the composition of the material, the antibacterial, antiviral, sterilizing and virucidal space charge electret material also has excellent biocompatibility. There is no difference between untreated textiles and textiles processed by BPEI space charge electret material in VERO cell proliferation. The elution from control textiles and textiles processed by space charge electret material moderately reduces the proliferation of vero E6 cells. There is no difference between untreated textiles and textiles processed by C-polar in VERO cell proliferation, and no reduction in cell sensitivity is found. These results confirm that space charge electret material is safe and suitable for industrial production and large-scale use.

[0027] For cationic polymers, the hydrophilic cationic bearing groups help attract negatively charged membranes via electrostatic attraction, while the hydrophobic alkyl chains help the cationic polymer chains insert into the membrane via hydrophobic and van der Waals interactions. The degree of hydrophobicity determines the extent to which the alkyl partitions penetrate into the lipid bilayer to destroy bacteria. Therefore, different cationic polymers have different levels of antimicrobial activity. However, there is currently a lack of highly effective quantitative techniques to evaluate the degree of antimicrobial activity of cationic polymers. In addition, there is currently little literature on the antiviral and virucidal effects of cationic polymers, especially for COVID-19.

[0028] Application of space charge electret materials

[0029] Space charge electret materials can be widely used in air filtration products (such as masks, protective clothing and air purifiers) and personal / household hygiene products such as hand sanitizers, wet wipes and toilet paper, home / hotel textiles, and related disposable products. Space charge electrets can help cut off the spread of viruses among the crowd, with high filtration efficiency (passive function) and self-disinfection (active function), and there is no need to worry about causing incidental environmental pollution or indirect / secondary collateral hazards when using them. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic illustration of the disinfection mechanism of space charge electret materials with high positive charge density.

[0031] Figure 2 The chemical structures of cationic polymers used to prepare space charge electret materials and their positive charge states are shown.

[0032] Figure 3 Surface modification of textile substrates with space charge electret materials to achieve high positive charge density is demonstrated.

[0033] Figure 4 The air filtration and self-disinfection functions of the textile substrate surface modified with space charge electret material are illustrated.

[0034] Figure 5 Flow chart of surface modification of textile substrate using BPEI space charge electret as an example.

[0035] Figure 6 Schematic illustration of the charge measurement setup used to evaluate the positive charging properties of space charge electret materials and their typical charge curves induced by repeated contact and separation controlled by repeated application and release of external force.

[0036] Figure 7 The effect of BPEI concentration on the charge density of BPEI-modified textiles is shown.

[0037] Figure 8 Typically shown is the instantaneous output voltage generated when a textile surface modified with a high positive charge density space charge electret material is subjected to repeated impact / contact.

[0038] Fig. 9 The virucidal performance of different textile substrates treated with BPEI space charge electret material at different solution concentrations is shown.

[0039] Fig.10 The test results of different materials for killing human coronavirus 229E are shown, and these different materials include paper towels, FFP2 filters, FFP2 sponges, Curie spunlace fabrics (i.e., cellulose / polyester textiles treated with BPEI space charge electret materials) and Curie paper (i.e., paper towels treated with BPEI space charge electret materials).

[0040] Fig.11 The test results of different materials for killing Coxsackievirus B6 are shown, including paper towels, FFP2 filters, FFP2 sponges, Curie spunlace fabrics (i.e., cellulose / polyester textiles treated with BPEI space charge electret materials), and Curie paper (i.e., paper towels treated with BPEI space charge electret materials).

[0041] Fig.12 It was shown that cellulose / polyester textiles treated with BPEI space charge electret material achieved a virus filtration efficacy of over 99.9%.

[0042] Fig.13 It was shown that cellulose / polyester textiles treated with BPEI space charge electret material killed Staphylococcus aureus with an efficacy exceeding 99.9%.

[0043] Fig.14The test results of killing Staphylococcus aureus before and after 60 washes of different textile substrates treated with BPEI space charge electret materials are shown. 100% cotton plain weave, 100% cotton after 60 washes, polyester / cotton (65% / 35%), polyester / cotton (65% / 35%) after 60 washes, polyester / spandex (92% / 8%), polyester / spandex (92% / 8%) after 60 washes are marked as sample numbers #1, #2, #3, #4, #5 and #6, respectively.

[0044] Fig.15 It was shown that cellulose / polyester textiles treated with BPEI space charge electret material achieved a bacterial filtration efficacy of over 99.9%.

[0045] Fig.16 Shown is the effect of cellulose textiles treated with different concentrations of BPEI space charge electret material on the viability of VEROE6 cells.

[0046] Fig.17 Shown is the effect of cellulose / polyester textiles treated with different concentrations of BPEI space charge electret material on the viability of VERO E6 cells.

[0047] Fig.18 The test results of the cytotoxicity of different concentrations of BPEI space charge electret material (C-POLAR) on GMK cells (left panel) and MRC5 cells (right panel) are shown.

[0048] Fig.19 The effect of cellulosic textiles treated with different BPEI space charge electret materials on cell sensitivity is shown.

[0049] Fig. 20 The effect of cellulose / polyester textiles treated with different BPEI space charge electret materials on cell sensitivity is shown.

[0050] Fig.21A Shown are the test results of ISO 10993-5 (in vitro cytotoxicity test) on textile substrates treated with BPEI space charge electret materials.

[0051] Fig. 21B Shown are the test results of ISO 10993-10 (animal skin irritation test) on textile substrates treated with BPEI space charge electret materials.

[0052] Fig. 21C Shown are the test results of ISO 10993-10 (Skin Sensitization Test) for textile substrates treated with BPEI space charge electret materials.

[0053] Fig. 22 A method of loading a space charge electret material on the surface of a textile substrate material is shown.

[0054] Fig.23 A general flow chart and preferred embodiments for the design and fabrication of cationic polymer-based space charge electret materials with high charge density for use in a wide range of antibacterial, antiviral, bactericidal, and virucidal applications.

[0055] Fig.24A The hydrogen bonding of a linear PEI to a fiber substrate (an example of a hydrophobic material) according to a preferred embodiment is schematically illustrated.

[0056] Fig. 24B The hydrogen bonding of a branched PEI to a fiber substrate (an example of a hydrophobic material) according to a preferred embodiment is schematically illustrated.

[0057] Fig.25A The mechanism by which three silyl linkers bond to a fiber substrate (an example of a hydrophobic material) and to each other via a single -O-linker and then bond to a linear PEI via epoxide ring opening according to an example embodiment is schematically illustrated.

[0058] Fig.25B The mechanism by which three silyl linkers according to an exemplary embodiment bond to a fiber substrate (an exemplary hydrophobic material) and to each other via a single -O-linker and then bond to a branched PEI via epoxide ring opening is schematically illustrated.

[0059] Fig.26A The process steps for bonding the cationic polymers of the present disclosure to textiles / fibers (ie, fibrous substrate materials) according to exemplary embodiments are schematically illustrated.

[0060] Fig.26B An exemplary schematic diagram of bonding a branched cationic polymer to a fibrous substrate material according to an exemplary embodiment is shown.

[0061] Fig.27A Shown are exemplary synthetic routes for preparing various silylated linear PEI compounds via silylation of linear PEI according to exemplary embodiments.

[0062] Fig.27B Exemplary synthetic routes for preparing various silylated branched PEI compounds via silylation of branched PEI according to exemplary embodiments are shown.

[0063] Fig.27C A synthetic route for reacting silylated linear PEI with a fiber substrate, an exemplary hydrophobic material, according to an exemplary embodiment is shown.

[0064] Fig.27D A synthetic route for reacting a silylated branched PEI with a fiber substrate, an exemplary hydrophobic material, according to an exemplary embodiment is shown. DETAILED DESCRIPTION

[0065] The present application is described in detail below in conjunction with the accompanying drawings and specific embodiments so that a person of ordinary skill in the art can make and use various embodiments. As an example, a description of a specific device, technology and application is provided. Various modifications to the examples described herein will be apparent to a person of ordinary skill in the art, and the general principles defined herein can be applied to other examples and applications without departing from the spirit and scope of the present invention. Therefore, the disclosed invention is not intended to be limited to the examples described herein, but is intended to conform to the full breadth and scope consistent with the claims.

[0066] definition

[0067] Unless otherwise defined, all technical and scientific terms used herein have the same literal meaning as commonly understood by those of ordinary skill in the art of the present application. The terms used in the specification of the present application are only for the purpose of describing or explaining a particular embodiment and are not intended to limit the present application. As used herein, the term "and / or" includes any and all combinations of one or more associated listed items.

[0068] Furthermore, the technical features mentioned in the various embodiments of the present application described below may be combined with each other as long as they do not contradict or conflict with each other.

[0069] As used herein, "electret" (the word is formed by electr- from "electricity" and -et from "magnet") refers to a dielectric material having a quasi-permanent macroscopic electric field at its surface. It can be divided into two different types of materials: dipole electret and space charge electret. Dipole electret is composed of electric dipoles, which are generally electrically neutral as a whole under other circumstances, but can cause a quasi-permanent electric field on a macroscopic level after the dipoles are aligned by an external force (such as via high-voltage polarization). Materials with a net macroscopic electrostatic charge are defined as space charge electrets, which can be easily generated by contact electrification. Due to the imbalance of charge, they have a quasi-permanent electric field on their surface. Electrets can be made by first melting a suitable dielectric material, such as a polymer or wax containing polar molecules, and then allowing it to resolidify in a strong electrostatic field. The polar molecules of the dielectric itself will align with the direction of the electrostatic field, producing a dipole electret with a permanent electrostatic bias. Any factor that disrupts the alignment of the polar molecules, such as high temperatures, leads to a weakening of the electrostatic field. Electrets can also be made by embedding excess charge into a highly insulating dielectric, for example with the aid of an electron beam, corona discharge, injection from an electron gun, electrical breakdown of a gap, or via a dielectric barrier.

[0070] The space charge electret material with antibacterial, antiviral, bactericidal and virucidal effects of the present invention has high positive charge density, amphiphilicity and biocompatibility. In some embodiments, the space charge electret material comprises one or more cationic polymers. In certain preferred embodiments, the space charge electret material comprising one or more cationic polymers comprises (C-POLAR) linear polyethyleneimine (PEI) and / or branched polyethyleneimine (BPEI). In some embodiments, the space charge electret material does not align molecular poles or embed excess charges. In some embodiments, due to the difference in the number of cationic and anionic charges, the space charge electret material or cationic polymer has a net static charge. In some embodiments, since the ionic groups are easy to transfer, the electric field of the space charge electret material can be further enhanced by contact electrification. In other embodiments, the space charge electret material has amphiphilicity. In some embodiments, the space charge electret material has a hydrophilic cation-bearing group and a long hydrophobic alkyl chain.

[0071] As used herein, the term "space charge density" or "charge density" refers to the amount of charge per unit surface area or unit contact area. The term "positive space charge density" or "positive charge density" refers to the total amount of positive charge minus negative charge per unit surface area or unit contact area.

[0072] As used herein, the term "electrical conductivity" or "conductivity" refers to the ability of a material to resist the flow of electric current. In some embodiments, electrical conductivity increases at low frequencies. In some embodiments, electrical conductivity decreases at high frequencies.

[0073] As used herein, the term "resistivity" or "resistivity" refers to the ability of a material to conduct electric current. It is the inverse of a material's electrical conductivity or conductivity.

[0074] As used herein, the term "surface energy" refers to the excess energy associated with the presence of a surface.

[0075] As used herein, the term "hydrophobic material" refers to a material containing at least one hydroxyl group at the surface that can react with amino groups. The hydroxyl group can be part of the molecular structure itself (as in the case of polyvinyl alcohol and its derivative copolymers), or the hydroxyl group can come from water molecules adsorbed on the surface of the material, for example due to atmospheric moisture. Most surfaces, regardless of their inherent hydrophobicity, have a thin film of water deposited on their surface. Even solids with surface energies less than 20 Nm m -1 Hydrophobic materials such as PTFE and poly(tetrafluoroethylene-co-hexafluoropropylene) (FEP) can also adsorb about 1.5-2.0 monolayers of water on their surfaces. In some embodiments, the hydrophobic material is a synthetic polymer. In some embodiments, the hydrophobic material is a synthetic polymer having at least one hydroxyl group. In some embodiments, the synthetic polymer has a more hydrophobic surface and contains fewer hydroxyl groups. In some embodiments, the solid surface energy of the synthetic polymer is between 28 and 48 mN m -1 between.

[0076] In some embodiments, the amino group is a part of the silyl joint of the present disclosure. Hydrophobicity can be measured by methods known to those skilled in the art, such as measuring the contact angle of a droplet on a material surface or calculating the solid surface energy. In some embodiments, the hydrophobic material is a synthetic polymer or a natural polymer. Examples of synthetic polymers include but are not limited to polyethylene (PE), polypropylene (PP) and polyethylene terephthalate (PET). In some embodiments, the hydrophobic material includes a natural polymer cellulose fiber or fabric containing a hydroxyl group. In some embodiments, the hydrophobic material is a mixture of a synthetic and natural polymer with suitable surface wettability. The surface wettability of the substrate can be adjusted by blending synthetic and natural polymer fibers. Examples of hydrophobic materials include, but are not limited to, cotton, linen, silk, wool, spunlace, chitosan, polyvinyl alcohol, polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), acrylonitrile butadiene styrene (ABS), poly (methyl methacrylate) (PMMA), aramid (such as nylon), silicone (such as polydimethylsiloxane), latex, glass, semi-fluorinated polymers and perfluorinated polymers (such as polytetrafluoroethylene (PTFE)). In other embodiments, the hydrophobic material is a polyester. "Polyester" is a polymer containing an ester functional group in each repeating unit of its main chain. Examples include, but are not limited to, polyethylene terephthalate (PET) and polybutylene terephthalate (PBT).

[0077] In some embodiments, the hydrophobic material is drawn as shown below with one or more hydroxyl groups. In some embodiments, the hydrophobic material is a fibrous substrate material. A fibrous substrate material is any material comprising cellulose fibers.

[0078]

[0079] It will be understood by those skilled in the art that the schematic diagram above is not intended to indicate that the hydrophobic material / fibrous substrate has only three -OH groups. Rather, the diagram is merely schematic and is intended to include many -OH groups, the number depending on the nature of the material.

[0080] As used herein, the term "C-POLAR" or "c-polar" refers to a positively charged / cationic polymer that can be applied to the surface of a hydrophobic material (e.g., a spunlace surface, a cotton surface, or a polyester surface). In some embodiments, "C-POLAR" or "c-polar" refers to an electret material (agent or solution) used in the surface modification of a textile substrate. In some embodiments, "C-POLAR" or "c-polar" is polyethyleneimine (PEI); in some embodiments, "C-POLAR" or "c-polar" is linear polyethyleneimine. In some embodiments, "C-POLAR" or "c-polar" is branched polyethyleneimine (BPEI). In some embodiments, "C-POLAR" or "c-polar" refers to a certain concentration range of PEI or BPEI. In some embodiments, "C-POLAR" or "c-polar" is 2-30% PEI or BPEI, 2-15% PEI or BPEI, 2-10% PEI or BPEI, 2-8% PEI or BPEI, 2-4% PEI or BPEI, 4-6% PEI or BPEI, 6-8% PEI or BPEI, 2%, 3%, 4%, 5%, 6%, 7% or 8% PEI or BPEI. In some embodiments, "C-POLAR" or "c-polar" is 2%, 4%, 6%, 8% or 10% PEI or BPEI. In some embodiments, "C-POLAR" or "c-polar" is a space charge electret material. For clarity, "C-POLAR" or "c-polar" when described in conjunction with a textile, such as "C-POLAR spunlace fabric" refers to a composition comprising a cationic polymer and a textile.

[0081] As used herein and in the claims, the term "antimicrobial composition" means a composition effective in (i.e., in a suitable form and amount) killing microorganisms or inhibiting their growth. In some embodiments, the antimicrobial composition is one or more space charge electret materials. In some embodiments, the antimicrobial composition is one or more cationic polymers. In some embodiments, the antimicrobial composition comprises C-POLAR or BPEI. In some embodiments, the antimicrobial composition comprises cotton and / or polyester.

[0082] As used herein and in the claims, the terms "comprising" (or any related forms such as "comprise" and "comprises"), "including" (or any related forms such as "include" or "includes"), "containing" (or any related forms such as "contain" or "contains") are meant to include the following elements but not exclude other elements. It should be understood that for each embodiment using the terms "comprising" (or any related forms such as "comprise" and "comprises"), "including" (or any related forms such as "include" or "includes"), the disclosure / application also includes alternative embodiments in which the terms "comprising", "including" or "containing" are replaced with "consisting essentially of" or "consisting of". These alternative embodiments using "consisting of" or "consisting essentially of are to be construed as narrower embodiments of the "comprising," "including," or "containing" embodiments.

[0083] As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. When a range is mentioned in the specification, the range should be understood to include every discrete point within the range. For example, 1-7 means 1, 2, 3, 4, 5, 6 and 7.

[0084] As used herein, the term "about" should be understood to be within the normal tolerance range of the art and not more than ±10% of the stated value. By way of example only, about 50 means 45 to 55, including all values ​​therebetween. As used herein, the expression "about" a particular value also includes that particular value, for example, about 50 includes 50.

[0085] As used herein, the term "cationic polymer" refers to a macromolecule having a cationic group in the polymer backbone and / or in the side chain, such as cationic peptides, (quaternary) ammonium salts, biguanides, phosphonium salts, guanidines, sulfonium and pyridinium salts. In some embodiments, the cationic polymer is macroscopically positively charged and generates a permanent macroscopic electric field at its surface. In some embodiments, the cationic polymer is a type of space charge electret material. In a particularly preferred embodiment, the cationic polymer comprises (C-POLAR) linear polyethyleneimine (PEI) and / or branched polyethyleneimine (BPEI).

[0086] As used herein, the term "amphiphilic" refers to the case where a molecule has both hydrophilic and hydrophobic regions, such as (in the case of a cationic polymer) a hydrophilic cation-bearing group and a long hydrophobic alkyl chain.

[0087] Antimicrobial compositions

[0088] One embodiment of the present disclosure provides an antimicrobial composition comprising a positive surface charge density of 2-35 nC cm -2 、Conductivity is less than 6x 10 at a frequency of 80kHz -7 sm -1 space charge electret material; and surface energy less than 50 mN m -1 or mJ m -2 hydrophobic material.

[0089] In some embodiments, the positive surface charge density is 5-10, 10-20, greater than 5.5, or greater than 9.59 nC cm -2 .

[0090] In some embodiments, the resistivity of the space charge electret material is greater than 1.67 x 10 6 Ω·m.

[0091] According to another embodiment of the present disclosure, the space charge electret material is a cationic polymer. In some embodiments, the cationic polymer is natural, semi-synthetic or synthetic; the cationic polymer has a linear, branched, hyperbranched or dendritic molecule-like structure; and the cationic polymer comprises at least one cationic carrying group located in the main chain or side chain of the polymer. In other embodiments, the cationic polymer is selected from gelatin, chitosan, cationic peptides, cationic cyclodextrins, cationic dextran, cationic cellulose, polyethyleneimine (including linear polyethyleneimine and / or branched polyethyleneimine), polylysine, polyamidoamine, poly(amino-co-ester) and poly[2-(N,N-dimethylamino)ethyl methacrylate]. In still other embodiments, the polymer is selected from the group consisting of the following: Figure 2 Those listed in .

[0092] According to another aspect of the present disclosure, the surface of the hydrophobic material comprises a cellulose structure having at least two components, and at least one component is slightly positively charged in polarity. In some embodiments, the surface energy of at least one of the at least two components is less than 50 mN m -1 In some embodiments, the surface of the hydrophobic material is highly dense, flat, uniform, and uniformly positively charged.

[0093] Connectors

[0094] In some embodiments, the cationic polymer is bonded to the hydrophobic material via a linker molecule. In some embodiments, the linker is C1-C 20 Aliphatic chain, where C1-C 20 0, 1, 2 or 3 carbon units of the aliphatic chain are replaced by one or more heteroatoms selected from -O-, -S- and -NR-; R is independently H or C1-C6 alkyl; and C1-C 20 At least one carbon unit of the aliphatic chain is bonded to a silyl group. In some embodiments, the silyl group is -Si(OR + )2. –Si(R + )2 or –Si(R + )(OR + ); each R + are independently selected from H and C1-C6 alkyl; or R + is a silyl group of another linker, wherein the silyl groups of two different linkers are linked together via a single -O- group. + are independently H or C1-C3 alkyl.

[0095] As an example, the figure below shows how three silyl linkers are bonded to a hydrophobic material and to each other via a single -O-linker.

[0096]

[0097] Si-C connector

[0098] According to another aspect, the silyl group is bonded to a carbon atom of the joint. In some embodiments, the carbon atom is a terminal carbon unit of the joint. A terminal carbon unit is a carbon unit in an aliphatic chain that is bonded to only one other unit in the aliphatic chain. For example, in a C4 carbon chain CH3CH2CH2CH3, the terminal carbon units will be the first and fourth carbon units.

[0099] Si-N connector

[0100] In some embodiments, the silyl group is bonded to the nitrogen atom of the linker. In some embodiments, the linker is C7-C 20 Aliphatic groups wherein 1, 2 or 3 carbon units of the linker are replaced with -NR-, -N= or -N(R)2, wherein each R is independently H or C1-C6 alkyl.

[0101] Based on the number of valence groups in the carbon group being replaced, one skilled in the art will understand which nitrogen group is a suitable replacement for the carbon group. For example, in the aliphatic group CH3CH2CH=CHCH2CH3, the first carbon atom will be replaced with –N(R)2, the second carbon atom will be replaced with –NR–, and the third carbon atom will be replaced with –N=.

[0102] In some embodiments, the linker together with the cationic polymer is

[0103]

[0104] Where R 0 is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2; and n is 0, 1, 2, 3 or 4.

[0105] In some embodiments, n>0. In some embodiments, n is 1, 2, 3, 4, 5, 6, 7, or 8. In some embodiments, n>0 and <100. In some embodiments, n is 0-10, 0-20, 0-30, 0-40, or 0-50. In some embodiments, n is 1-20.

[0106] Linker + Cationic Polymer Example

[0107] Additional example embodiments of linkers with cationic polymers:

[0108]

[0109]

[0110] Other connectors

[0111] According to another aspect, the linker is C7-C 10 In some embodiments, the linker is optionally substituted with one or more J groups, wherein J is OR 0 , SR 0 or N(R 0 )2, where R 0 is H or C1-C6 alkyl. In certain exemplary embodiments, the linker is -Si(OR + )2-(CH2)3OCH2CH(OR 0 )CH2-.

[0112] In other exemplary embodiments, the linker is -Si(OR + ) 2. In still other exemplary embodiments, the silyl group is covalently bonded to the hydroxyl group of the hydrophobic material.

[0113] Method for modifying the surface of hydrophobic material

[0114] Another aspect of the present disclosure provides a method for modifying the surface of a hydrophobic material with a space charge electret material, comprising the following steps:

[0115] (a) dissolving a space charge electret material in a suitable solvent;

[0116] (b) introducing a mixture of space charge electret material / suitable solvent onto the surface of the hydrophobic material by dip coating and / or spray coating;

[0117] (c) removing the suitable solvent by a tensioning process and / or drying in air or at a drying temperature; and

[0118] (d) optionally performing one or more systematic tests and evaluations on the surface of the hydrophobic material by contact electrification performance evaluation, antiviral test, antibacterial test, virus filtration test and / or bacterial filtration test.

[0119] Another aspect of a preferred embodiment of the present disclosure is a method for modifying the surface of a hydrophobic material, comprising the steps of:

[0120] (a) dissolving a space charge electret material in a suitable solvent to form a space charge electret material / suitable solvent mixture;

[0121] (b) introducing a space charge electret material / suitable solvent mixture onto the surface of the hydrophobic material by dip coating and / or spray coating;

[0122] (c) subjecting the hydrophobic material to a tensioning process and / or drying the material at air temperature or elevated drying temperature; and

[0123] (d) optionally performing one or more systematic tests and evaluations on the surface of the hydrophobic material by contact electrification performance evaluation, antiviral test, antibacterial test, virus filtration test and / or bacterial filtration test.

[0124] In some embodiments, the space charge electret material is branched polyethyleneimine (BPEI), linear polyethyleneimine (LPEI or PEI), dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, cationic cellulose, didecyldimethylammonium chloride, or a combination thereof.

[0125] In some embodiments, the space charge electret material is LEI or BPEI.

[0126] In some embodiments, the concentration of the space charge electret material in a suitable solvent is 0.195% to 10%.

[0127] In some embodiments, the suitable solvent is water, ethanol or a mixture thereof. In some embodiments, the suitable solvent is water. In selected preferred embodiments, the space charge electret material is dissolved in a solvent without added salt. In some embodiments, the hydrophobic material is cellulose or cellulose / polyester nonwoven fabric.

[0128] In some embodiments, a tensioning process is applied, wherein the tensioning process includes one or more actions of stretching, steaming, heating, pressing, or subjecting the material to pressure (including high air flow pressure or mechanical pressure). In some preferred embodiments, pressure is applied to the material by adjustable rollers. In some preferred embodiments, heating is provided by an oven.

[0129] In some embodiments, the drying temperature is below 100° C. In some embodiments, the drying temperature is 50° C.-100° C., 100° C.-200° C., 150° C.-200° C., 150° C.-175° C., 175° C.-200° C., 150° C.-170° C., or 155° C.-165° C. In some preferred embodiments, the drying temperature is 160° C.

[0130] In some embodiments, the one or more system tests and evaluations are contact electrification performance evaluations, antiviral tests, antibacterial tests, virus filtration tests, bacterial filtration tests, or combinations thereof.

[0131] Method for loading space charge electret material

[0132] Another aspect of the present disclosure provides a method for loading a space charge electret material onto a surface of a hydrophobic material, comprising the steps of:

[0133] (a) carding at least one of the at least two components to form a drylaid web;

[0134] (b) loading a space charge electret material onto the fabric surface of the drylaid web by a high pressure liquid stream; and

[0135] (c) drying and winding the drylaid web so that the space charge electret material forms a crosslinking agent with the fabric surface to form a surface of a hydrophobic material.

[0136] In some embodiments, the hydrophobic material comprises knitted, woven, nonwoven or mixed textile fibers. In some embodiments, the textile fibers comprise hydrophilic natural fibers and hydrophobic synthetic fibers (e.g., blended fibers). In some embodiments, the textile fibers comprise cotton, wool, cellulose, spunlace, synthetic polyester, polypropylene, polyethylene, nylon or a blend of at least two thereof. In some embodiments, at least one of the components is cotton or polyester. In some embodiments, another component is cotton or polyester, provided that the two components are not identical. In some embodiments, the ratio of the two components is 65% polyester / 35% cotton or 50% polyester / 50% cotton.

[0137] In some embodiments, the cationic polymer comprises 0.195 wt % to 15 wt % of the total antimicrobial composition.

[0138] Method for preparing joint composition

[0139] Some embodiments of the present disclosure provide a method for preparing an antimicrobial composition having a linker molecule, comprising the following steps:

[0140] a) mixing a silylated epoxy compound IIa with a hydrolyzing agent in the presence of water to form a compound IIb;

[0141]

[0142] Wherein each R is independently a C1-C6 alkyl group;

[0143] b) heating compound IIb and hydrophobic material IIc to form compound IId;

[0144]

[0145] c) Combining compound IId with cationic polymer IIe under epoxide ring opening conditions

[0146]

[0147] To form an antimicrobial composition of Formula II (presented first below) or II':

[0148] and / or

[0149]

[0150] in

[0151] Each R is independently H or C1-C6 alkyl; or R is a silyl group of another linker; and

[0152] R Xis H or is another linker.

[0153] In some embodiments, the further linker is formed via an epoxide ring-opening reaction. In some embodiments, multiple linkers are connected as shown in the following figure:

[0154]

[0155] Hydrolyzing agents are well known to those skilled in the art and may include acids or bases. For the sake of clarity, an acid is a molecule that can provide a proton. Examples include hydrochloric acid (HCl), hydroiodic acid (HI), hydrobromic acid (HBr), perchloric acid (HClO 4 ), nitric acid (HNO 3 ) and sulfuric acid (H 2 SO 4 ). In some embodiments, an acid can hydrolyze a molecule together with water, i.e., replace other groups with water molecules. Other embodiments in which the hydrolyzing agent is an acid or base, a weak acid or a weak base (as defined above) also provide examples and scope below.

[0156] In some embodiments, the hydrolysis agent is "pH adjusted" water. The pH of the water can be adjusted by adding a weak acid (such as acetic acid) or a weak base (such as ammonia) to achieve the hydrolysis of IIa to IIb. In some embodiments, the concentration of acetic acid in water ranges from 0.02% to 1%. In other embodiments, the concentration of ammonia is between 0.25% and 3%. In some embodiments, the hydrolysis reaction is carried out at a temperature below 50°C, and in some embodiments, at a temperature of 20-50°C.

[0157] Epoxide ring opening conditions are known to those skilled in the art and typically involve the use of Lewis acids such as trimethylborane, alumina, and lithium perchlorate. In some embodiments, at least one Lewis acid is added and used as a catalyst to activate the ring opening of the epoxide through the amino group of another molecule. In some embodiments, the epoxide ring opening reaction is carried out at a temperature of 60°C-150°C for a duration of 5 minutes to 3 hours. Those skilled in the art will appreciate that in some embodiments, the epoxide ring opening reaction can be carried out in the absence of a Lewis acid. For example, in some embodiments, microwave irradiation is used for post-treatment to increase the grafting rate of linear / branched polyethyleneimine grafted to the surface of a modified substrate containing epoxy groups.

[0158] Examples of compounds of Formula IIa are shown below:

[0159]

[0160]

[0161] The cationic polymers described herein contain many amino groups, and the hydrophobic material treated with the epoxy-silyl linker (compound of formula IId) also includes several reactive epoxy sites. Therefore, there are many ways in which the amino groups of the cationic polymer can react with the hydrophobic material through the linker described herein via one or more epoxide ring-opening reactions. Sometimes, two amino groups in the same polymer repeating unit of the cationic polymer can react with the epoxy groups on two different silyl linkers and thereby bond with two different hydroxyl groups of the hydrophobic material, as shown in the schematic diagram below.

[0162]

[0163] Those skilled in the art will appreciate that there are a variety of ways in which the amino groups of the cationic polymer can react with the various epoxy groups in the compound of Formula IId.

[0164] Another embodiment of the present invention provides a method for preparing an antimicrobial composition having a linker, comprising the following steps:

[0165] d) hydrolyzing compound IIIa in the presence of water and an acid to form compound IIIb;

[0166]

[0167] Wherein R is an aliphatic group;

[0168] e) heating the hydrolyzed compound IIIb and the hydrophobic material IIIc together:

[0169]

[0170] To form an antimicrobial composition of Formula III:

[0171]

[0172] Where L 1 and L 2 Each is independently H or a silyl group of another linker bonded to the same hydrophobic material.

[0173] In some embodiments, the compound of IIIa is

[0174]

[0175] Wherein R=CH3, CH2CH3, CH2CH2CH3, CH(CH3)2; n is 0, 1, 2, 3 or 4.

[0176] In some embodiments, the compound of Ilia is selected from the compounds in Table Ilia.

[0177] Table IIIa

[0178]

[0179]

[0180] In some embodiments, the hydrophobic material IIIc comprises a plurality of hydroxyl (OH) units, and therefore, the hydrolysis compound IIIb can react with the hydroxyl groups in a variety of ways. In some exemplary embodiments, one or more silyl groups can be bonded to each other through oxygen atoms, as shown in the schematic diagram below.

[0181]

[0182] Another aspect of the present disclosure provides a method for preparing an antimicrobial composition having a linker, comprising the following steps:

[0183] a) making the cationic polymer Iva

[0184]

[0185] Reaction with a silylating agent Z-Cl, wherein

[0186] Z is SiR(OR)2, Si(R)2(OR) or Si(OR)3; and

[0187] Each R is independently a C1-C6 alkyl group;

[0188] To form compound IVb; wherein compound IVb is

[0189]

[0190] Each R is independently a C1-C6 alkyl group;

[0191] b) mixing compound IVb with an acid in the presence of water to form compound IVc; wherein compound IVc is

[0192]

[0193] Each R is independently a C1-C6 alkyl group;

[0194] c) heating compound IVc and hydrophobic material IVc together

[0195]

[0196] To form an antimicrobial composition of Formula IV:

[0197]

[0198] Another aspect of the present disclosure provides a method for preparing an antimicrobial composition having a linker, comprising the following steps:

[0199] a) cationic polymer Va

[0200]

[0201] Reaction with a silylating agent Z-Cl, wherein

[0202] Z is SiR(OR)2, Si(R)2(OR) or Si(OR)3; and

[0203] Each R is independently a C1-C6 alkyl group;

[0204] To form compound Vb;

[0205] wherein compound Vb is a compound of formula Va in which one or more nitrogen units are silylated with one or two Z groups;

[0206] b) mixing compound Vb with an acid in the presence of water to form compound Vc; wherein compound Vc is a compound of Vb wherein R is H;

[0207] c) heating the compound Vc together with a hydrophobic material Vd comprising at least one OH group;

[0208]

[0209] d) to form the antimicrobial composition claimed thereto.

[0210] Silylation agent

[0211] Silylating agents are known to those skilled in the art and are agents that aid in the addition of a silyl group to another molecule. In some embodiments, the silylating agent is Z-Cl, wherein Z is SiR(OR)2, Si(R)2(OR), or Si(OR)3; and each R is independently a C1-C6 alkyl group;

[0212] In some embodiments, each R is independently CH3, CH2CH3, CH2CH2CH3, or CH(CH3)2.

[0213] Example embodiments of antimicrobial compositions having Si linkers are shown in Table V:

[0214] Table V

[0215]

[0216]

[0217]

[0218] In some embodiments, compound IVb is selected from the compounds of Table IV.

[0219] Table IV

[0220]

[0221]

[0222]

[0223]

[0224]

[0225] wherein each R is independently a C1-C6 alkyl group.

[0226] Methods of killing microorganisms

[0227] Another aspect of the present disclosure includes providing a method of killing microorganisms, comprising filtering air containing microorganisms through an antimicrobial composition of the present disclosure to produce 95% to 99.9% microorganism-free air. In some preferred embodiments, the air is 99-99.9% microorganism-free. In some most preferred embodiments, the air is 99.9% microorganism-free.

[0228] In some embodiments, the microorganism has a mean particle size (MPS) of 1-10 μm. In some embodiments, the microorganism has a MPS of 1-5 μm. In some embodiments, the microorganism has a MPS of 3.0 ± 0.3 μm.

[0229] In some embodiments, air moves through the antimicrobial space charge electret material at an air flow rate of at least 20 L / min. In some embodiments, the air flow rate is 20-50 L / min. In some embodiments, the air flow rate is 28.3 L / min.

[0230] In some embodiments, the microorganism is a bacterium or a virus. In some embodiments, the virus is SARS-CoV-2, SARS-229E, Coxsackievirus-B6, or influenza virus. In some embodiments, the bacterium is Staphylococcus aureus.

[0231] Another aspect of the present disclosure provides a method of killing microorganisms, comprising contacting a space charge electret material with a microorganism for at least 1-5 minutes of incubation time to kill 99.9% of the microorganisms. In some embodiments, the microorganism is a bacterium and the incubation time is at least 1 minute. In some embodiments, the microorganism is a virus and the incubation time is at least 5 minutes. In some embodiments, the virus is SARS-CoV-2, SARS-229E, Coxsackie virus-B6 or influenza virus. In some embodiments, the bacterium is Staphylococcus aureus. For clarity, as described herein, "contact" means bringing the microorganism so close to the antimicrobial composition that the high positive charge density of the space charge electret material captures and kills the microorganism or microorganism.

[0232] Methods for measuring space charge density

[0233] Another aspect of the present disclosure provides a method for measuring space charge density on a test material, comprising the steps of:

[0234] (a) positioning a test material between a bottom acrylic plate including an adhesive electrode layer and an upper acrylic plate including a reference material / electrode layer of a charge measurement apparatus, and connecting an electrometer to the adhesive electrode layer and the reference material / electrode layer and adhering the test material to the adhesive electrode layer;

[0235] (b) repeatedly contacting and separating the upper acrylic plate with the bottom acrylic plate using a machine while repeatedly measuring the charge value using an electrometer to obtain one or more charge curves;

[0236] (c) calculating the charge value difference by subtracting the minimum charge value from the maximum charge value; and

[0237] (d) Determine the space charge density on the test material by dividing the difference in charge values ​​by the contact area of ​​the test material between the bonded electrode layer and the reference material / electrode layer.

[0238] In some embodiments, the reference material is a polytetrafluoroethylene (PTFE) membrane.

[0239] In some embodiments, the bonded electrode and the reference material / electrode layer have the same dimensions.

[0240] Antimicrobial Products

[0241] Another aspect of the present disclosure is to provide an antimicrobial product comprising and in combination with the antimicrobial composition of any one of the preceding embodiments. In some embodiments, the antimicrobial cargo product is an air conditioning system, an air conditioning unit, an air purifier, a disinfected fabric, a disinfected suit (PPE), a mask, a reusable disinfected mask, an air filter, a HEPA filter, a HEPA filter for an electric vehicle, an automatic fabric, an automotive interior material, a disinfected material, a disinfected suit, a disinfected glove, or a hand disinfectant.

[0242] In some embodiments, the two components on the surface of the hydrophobic material are cotton and cellulose; and the space charge electret material comprises branched / linear polyethyleneimine, chitosan, poly-L-lysine or poly-D-lysine. In some embodiments, cellulose is polyester; and the space charge electret material comprises branched polyethyleneimine (BPEI) or linear polyethyleneimine. In some embodiments, the two components on the surface of the hydrophobic material are 50% cotton and 50% polyester; and the space charge electret material comprises 2%, 3%, 4%, 5%, 6%, 7%, 8% and 9% of one or more of branched polyethyleneimine (BPEI) or linear polyethyleneimine. In some embodiments, the two components on the surface of the hydrophobic material are 50% cotton and 50% polyester; and the space charge electret material comprises 8% branched polyethyleneimine (BPEI) or 8% linear polyethyleneimine (PEI). In some embodiments, the antimicrobial composition further comprises 8.7% poly(diallyldimethylammonium chloride), 19.7% polyacrylamide; and / or 3.1% ammonium polyphosphate.

[0243] Exemplary embodiments of the present invention

[0244] Methods of killing microorganisms

[0245] refer to Figure 1, the main disinfection mechanism of space charge electret materials with high positive charge density to capture and kill microorganisms (such as bacteria and viruses), in addition to contact destruction determined by the degree of amphiphilicity and hydrophobicity, is also based on the coupling and synergy of contact electrification and non-contact electrostatic interaction. A study conducted by the Weizmann Institute of Science in Israel showed that the net charge of most proteins such as microorganisms (bacteria and fungi) and viruses is negatively charged. They are usually in the formation of protein envelopes. First, space charge electret materials with high positive charge density attract biohazards (such as bacteria and viruses) with negatively charged proteins via non-contact electrostatic interactions, resulting in an increase in contact / collision rate. Then contact electrification occurs when the drifting negatively charged biohazard collides with the positively charged electret, resulting in a sharp change in electrostatic potential and a sudden increase in electric stress. The electrostatic field lines leave the high positive charge surface of the space charge electret material, very directional and strongly seek the negatively charged surface of the biohazard, thereby generating very uneven electric stress on the surface of the biohazard. Strong electrostatic field tightly fixes biohazards on positively charged surface, and the generated non-uniform electric stress thus contributes to the shearing of envelope proteins and / or other key viruses or microbial proteins of biohazards. In the process of close contact, the hydrophobicity of amphiphilic space charge electret material also helps its lipophilic partition to be inserted into the film via van der Waals interaction. Therefore, the amphiphilic space charge electret material with high positive charge density can capture and kill biohazards by tearing off the envelope proteins and / or other key microbial proteins of biohazards based on the coupling effect of non-contact electrostatic interaction, contact electrification and van der Waals interaction. This new capture and disinfection mechanism mainly uses electric charge (+ / -) and the electrostatic field generated by it to create physical barriers and destruction. Therefore, no additional energy or chemicals are needed to prevent microorganisms or viruses from penetrating the surface. The cationic polymer selected for space charge electret material is also nontoxic. Although this barrier can be applied and used in many ways, an example of how to use it is to apply polymer to air filter. When correctly performed, it will capture and retain microorganisms and viruses, preventing them from passing through the filter and entering the filtered air.

[0246] Space Charge Electret Materials

[0247] The space charge electret material disclosed herein is composed of one or more cationic polymers. Figure 2Cationic polymers are a type of macromolecule containing cationic groups, such as linear polyethyleneimine (PEI or LPEI), polylysine (PLS), branched polyethyleneimine (BPEI), chitosan (CS), cationic cellulose (CCL), polyamidoamine (PADAM), poly(amino-co-ester) (PAE) and poly[2-(N,N-dimethylamino)ethyl methacrylate] (PDAMEMA). In some embodiments, cationic polymers have protonatable primary, secondary or tertiary amine functional groups, such as (quaternary) ammonium salts, biguanides, guanidines and pyridinium salts. In some embodiments, cationic polymers contain non-amine cationic groups such as phosphonium salts and sulfonium. Cationic polymers can be natural, semi-synthetic and synthetic, and their polymer structures can be linear, branched, hyperbranched or dendritic. The cationic carrying group can be located in the main chain or in the side chain. In some embodiments, the cationic polymer is gelatin, chitosan, a cationic peptide, a cationic cyclodextrin or a cationic dextran. In some embodiments, cationic polymers are used to make space charge electret materials.

[0248] Different cationic polymers have different positive charge densities. Other embodiments provide compositions of space charge electret materials having a high positive charge density surface to meet specific requirements of target applications. Positive charge density plays a key role in the degree of antibacterial and antiviral activity of textile substrates treated with space charge electret materials. In selected preferred embodiments, the space charge electret material bonded to a hydrophobic substrate material such as a textile is characterized by a uniform or substantially uniform positive charge density over the entire surface area of ​​the material. In some embodiments, the space charge electret material has a positive charge density of 9.59 nC cm -2 The disinfection effect increases with the increase of positive charge density. Figure 9-11 and 13 showed that space-charge electret materials with both high positive charge density and suitable hydrophobicity were found to have excellent antibacterial, antiviral, bactericidal, and virucidal effects against Staphylococcus aureus, SARS-229E, SARS-CoV-2, and Coxsackievirus B6, with an efficacy of more than 98% within 5 minutes.

[0249] Application of space charge electret materials

[0250] Space charge electret materials can be applied and used in many ways for antibacterial, antiviral, bactericidal and virucidal applications. Figure 3Surface modification of textile substrates with space charge electret materials to obtain high positive charge density to obtain antiviral and antibacterial textiles is illustrated. In a preferred embodiment, surface modification of textile substrates with space charge electret materials produces uniform or substantially uniform (equal, constant or substantially equal and / or constant) high positive charge density on the entire surface of the material. The material of the textile substrate can be natural cotton, wool, cellulose, synthetic polyester, nylon and their blends. The structure of the textile substrate can be knitted, woven and non-woven. Blended textile substrates refer to textile substrates woven or knitted with two or more different textile substrates. Their hydrophobicity or amphiphilicity can be adjusted by blending. The textile substrate contains both hydrophilic fiber regions and hydrophobic fiber regions, but together exhibits overall hydrophobic or hydrophilic properties. In other words, the blended textile substrate contains both hydrophilic fibers and hydrophobic fibers. When the blended hydrophobic fibers are more than the hydrophilic fibers, the final surface wettability of the 2D knitted / woven textile substrate should be hydrophobic. The influence of fabric structure also plays a key role, such as 3D spacer fabrics. Their surface wettability mainly depends on the surface layer. When the surface layer is knitted with 100% hydrophilic fibers, they are hydrophilic. Their surface wettability can also be adjusted by controlling the fiber composition of the surface layer like 2D fabrics. Based on the material and structure of the textile substrate used, space charge electret materials with antibacterial, antiviral, bactericidal and virucidal effects can be used in filtration products such as masks, protective clothing and air purifiers with new self-disinfecting functions, which can maintain high air permeability and particle / bacteria / virus filtration efficacy. They can also be used in personal and household hygiene products such as hand sanitizers, wet wipes and toilet paper, home / hotel textiles, and related disposable products.

[0251] refer to Figure 4, which illustrates and illustrates the use of space charge electret materials for high efficiency air filters with unique self-disinfection function. The textile fibers treated with amphiphilic space charge electret materials are three-dimensional, conformal, and positively charged. When biohazards (such as bacteria and viruses) pass through textiles, the fiber network plays an interception role, and the fiber surface with high positive charge captures negatively charged biohazards via non-contact electrostatic interaction / attraction. The strong electrostatic field causes the biohazards to collide with the fiber surface to produce a sudden increase in electrical stress via contact electrification, and is tightly fixed on the positively charged fiber surface. Finally, by the coupling effect based on non-contact electrostatic interaction, contact electrification and van der Waals force interaction, the protein envelope and / or other key viruses or microbial proteins of the biohazards are torn off / cut off, destroying the biohazards. Therefore, by selecting a suitable textile substrate to load the space charge electret material, an air filter with a unique self-disinfection function can be developed. These air filters of the present invention can capture bacteria and viruses, prevent them from passing through the filter into the filtered air, and can kill bacteria and viruses to avoid contact infection.

[0252] Method for preparing antimicrobial composition

[0253] refer to Figure 5, a flow chart for surface modification of textile substrate materials with space charge electret materials is illustrated based on the use of branched polyethyleneimine (BPEI) as a single-component space charge electret. First, the BPEI space charge electret is dissolved in a suitable solvent to the desired concentration. Suitable solvents for BPEI include, but are not limited to, water, alcohols (such as ethanol) and mixtures thereof. BPEI can be dissolved in a suitable solvent such as water or ethanol at any concentration. For example, a suitable solvent can be at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95% or 100% ethanol (or water). In other words, a suitable solvent can be no more than 95%, no more than 90%, no more than 80%, no more than 70%, no more than 60%, no more than 50%, no more than 40%, no more than 30%, no more than 20% or no more than 10% ethanol (or water). In some examples, any combination of these is also possible, for example, a suitable solvent may be 10 to 20%, 30 to 70%, or 50 to 95% ethanol. In some embodiments, a suitable solvent is water, including up to 100% water. In some embodiments, the concentration of BPEI used for surface modification of textile substrate materials is in the range of 1%-10%. For example, the BPEI concentration may be about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, or about 10%. For further example, the BPEI concentration may be at least 1%, at least 2%, at least 3%, at least 4%, at least 5%, at least 6%, at least 7%, at least 8%, or at least 9%. In other words, the BPEI concentration may be no more than 10%, no more than 9%, no more than 8%, no more than 7%, no more than 6%, no more than 5%, no more than 4%, no more than 3%, or no more than 2%. In selected preferred embodiments, any combination of these is also possible, for example, the BPEI concentration may be between 1-2%, 3-7% or 5-9%. In other selected embodiments, linear polyethyleneimine is used as the space charge electret material, including in concentrations that are respectively related to the concentration of BPEI in the preferred embodiments.

[0254] Secondly, BPEI is introduced to the desired textile substrate material by dipping or spraying. Preferred textile substrate materials relate to cellulose and cellulose / polyester nonwoven fabrics. Thirdly, it is necessary to remove the solvent from the textile substrate loaded with the BPEI solution, which can be carried out by drying in air or by drying at high temperature to evaporate the solvent faster. Preferably, the drying temperature should not exceed 100 ° C. Finally, the textile substrate material (BPEI modified textile) modified with BPEI space charge electret can be used for system testing and evaluation, such as contact electrification performance evaluation, antiviral test, antibacterial test, virus filtration test and bacterial filtration test.

[0255] Methods for evaluating contact electrification performance

[0256] Figure 6 The charge measuring device for evaluating the contact electrification performance of space charge electret material and the typical charge curve caused by repeated contact and separation controlled by repeatedly applying and releasing external force are schematically illustrated. Specifically, the method for measuring the positive charge of space charge electret material is based on a double-layer device consisting mainly of a bottom acrylic plate fixed with an adhesive electrode layer and an upper acrylic plate fixed with a reference material / electrode layer of the same size. In some embodiments, the adhesive electrode layer (and therefore the reference material / electrode layer of the same size) is 6cm×6cm. In other embodiments, an adhesive electrode layer with other dimensions and surface dimensions is used. In some embodiments, a PTFE membrane is fixed as a reference material. For example, other materials such as polydimethylsiloxane (PDMS) can be fixed as a reference material. Different reference materials give different measurement (reference) values. PTFE has high electronegativity and is particularly effective as a reference material for measuring the positive charge performance of other test samples. The test sample can be a woven / knitted / non-woven fabric sample and a membrane. The material of textile / fabric substrate can be natural cotton, wool, cellulose, synthetic polyester, nylon and / or their blends. The structure of textile / fabric substrate can be knitted, woven and / or nonwoven. During the test, the sample (such as a nonwoven textile substrate modified with a space charge electret material surface) is flatly and tightly adhered to the bonding electrode on the bottom acrylic plate. The upper acrylic plate can be controlled by a machine to repeatedly contact / impact the bottom acrylic plate. This allows the surface of the space charge electret material modified textile to contact the PTFE surface by external pressure, and allows them to separate after the external pressure is released. An electrometer is connected to the electrode to monitor and measure the charge change in real time. The stable charge curve measured by repeated contact and separation is recorded for further analysis. Generally, the maximum charge value occurs during the contact state, and the minimum charge value occurs during the separation state. The charge value difference during the contact and separation state can be regarded as the positive charge generated by contact electrification. The positive charge density is calculated by dividing the effective contact area (such as 6cm x6cm) with a positive charge, and can be used to quantitatively evaluate the degree of contact electrification. In other words, the charge density (σ) can be calculated by σ = Q / S, where Q is the total charge and S is the surface area.

[0257] Space charge electret material concentration and charge density of textile substrate

[0258] Figure 7The effect of the concentration of a single component space charge electret material (e.g., BPEI) on the charge density of a textile substrate is shown. A 40 g sample of spunlace (50% cotton / 50% polyester) was used as a textile substrate to introduce a given amount of space charge electret material. The aqueous solution concentration of the BPEI space charge electret for surface modification of the textile substrate was in the range of 0-30 wt%. Reference Figure 7 , when the C-polar (e.g. BPEI) concentration varies between 0% and 8 wt%, the charge density increases exponentially, which is attributed to the constructive interference on the spunlace surface. However, when the C-polar concentration is between 8 wt% and 30 wt%, the charge density decreases significantly, because the overload of C-polar destroys the texture and microstructure of the spunlace and disrupts the constructive interference of polarity.

[0259] Different single-component space charge electret materials have different positive charge density values. Some examples are shown in Table 1.

[0260] Table 1. Positive charge density of textile substrates treated with various single-component space charge electret materials.

[0261]

[0262]

[0263] Therefore, the positive charge density of the textile substrate can be tuned by adjusting the solution concentration and composition of the space charge electret material.

[0264] In order to obtain a modified textile with a high positive charge density, a single-component space charge electret material with a high charge density and a suitable concentration can be selected. In order to obtain a modified textile with a suitable positive charge density and hydrophobicity, a multi-component space charge electret material can be selected based on the different types of cationic polymers and components. The selection of cationic polymers with higher hydrophobicity can use polymers with low density cationic groups and long alkyl chains. In a selected preferred embodiment of the present invention, the high positive charge density of the modified textile is uniformly or substantially uniformly applied and obtained over the entire surface area of ​​the textile.

[0265] Figure 8 The transient output voltage generated when the textile surface modified with a space charge electret material with high positive charge density is repeatedly touched / impacted is shown. This result confirms the dramatic change of electrostatic potential during contact electrification.

[0266] Antiviral effect

[0267] refer to Fig. 9, the antiviral activity test against SARS-CoV-2 on textile substrates treated with space charge electret materials (i.e., BPEI spunlace fabrics) was adopted from ISO 18184. First, 50 μl of SARS-CoV-2 (100,000 PFU / ml) was added to 1 x 1 cm 2 The textile substrate materials treated with space charge electret materials and controls were in triplicate. The test textile substrates were incubated at room temperature with a glass cover for 5 minutes or 30 minutes. After incubation, the test textile substrates were transferred to 5 ml of DMEM complete medium, vortexed 5 times for 5 seconds each, and 200 μl of the medium was transferred to VERO-E6 cells, and the titer of the remaining virus was determined by plaque assay. The viruses in the 24-well plates were gently mixed with the cells (250,000 cells / well) and incubated at 37°C in a CO2 incubator for 4 hours. Afterwards, 0.4 ml of 3% carboxymethyl cellulose was added and then incubated for 5 days. After incubation, the cells were washed, stained with naphthol blue-black dye, washed with water and dried to count plaques. The titer is expressed in pfu / ml and the reduction in virus yield is expressed as a percentage, as Fig. 9 As shown in. The virucidal performance of different textile substrates (e.g., cellulose and cellulose / polyester substrates) treated with C-Polar (BPEI) (i.e., 4%, 6% or 8% BPEI space charge electret materials) of different solution concentrations is summarized. In short, cellulose / polyester textiles treated with BPEI show overall better virucidal efficacy than cellulose textiles treated with BPEI. Cellulose / polyester textiles treated with 6% BPEI space charge electret materials eliminated 98% of SARS-CoV-2 after exposure for 5 minutes and 99.6% of SARS-CoV-2 after exposure for 30 minutes, respectively. 100% virus elimination was achieved in one of the biological repeat studies. The reason can be attributed to the synergistic effect of the high positive charge density of BPEI modified fabrics and suitable lipophilicity (i.e., hydrophobicity). Due to the hydrophobic component of polyester, cellulose / polyester blended textiles generally show higher hydrophobicity than single-component cellulose textiles. As stated above, the hydrophobicity of amphiphilic materials also plays an important role in inserting their lipophilic partitions into the membrane via van der Waals interactions. This lipophilicity helps to enhance the electrical stress generated by the strong electrostatic field to tear off the envelope proteins of the biohazard and / or other key viral or microbial proteins of the biohazard (ref. Figure 1 and paragraph

[0085] ). Proper increase of BPEI can significantly increase the positive charge density, but also increase the hydrophilicity of the textile substrate. Excessive increase of BPEI leads to embedding into the hydrophobic surface of the textile and reducing lipophilicity, thereby slightly reducing the virucidal efficacy.

[0268] refer to Fig.10 and Fig.11 , the antiviral activity test of textile substrates treated with space charge electret materials (such as 4% BPEI spunlace cloth or 4% C-POLAR spunlace cloth) against human coronavirus 229E and coxsackie virus B6 was carried out. First, a 2.5x 2.5cm test textile material piece was soaked in 200μl of buffer containing virus (50000PFU) and incubated at room temperature for 5 minutes or 60 minutes respectively. Then the tube containing the test textile material and buffer was centrifuged. After removing the test textile material from the buffer, the viral concentration of the buffer was tested using RT-qPCR. The test results of different textile materials killing human coronavirus 229E and coxsackie virus B6 are shown. The textile materials used include paper towels (100% cellulose), FFP2 filters (non-woven polyester), FFP2 sponges (non-woven), Curie spunlace cloth (i.e. cellulose / polyester textiles treated with 4% BPEI space charge electret material) and Curie paper (i.e. cellulose treated with 4% BPEI space charge electret material). Both cellulose textiles and cellulose / polyester treated with BPEI showed surprisingly good virus-killing performance than those textiles without BPEI space charge electret materials (such as paper towels, FFP2 filters and FFP2 sponges). Most surprisingly, the results showed that the textile substrates treated with BPEI were 10,000 times more effective in antiviral activity than conventional filter media. In addition, the fact that similar effects were obtained for two viruses with different structural aspects (enteroviruses and coronaviruses) shows that the BPEI space charge electret materials on both polyester / cellulose and cellulose textile substrates are effective in eliminating different types of viruses. These two viruses represent enveloped viruses (coronaviruses with lipid bilayer structures) and non-enveloped viruses (enteroviruses with capsid structures), which means that their surface structures are very different. In addition, even after the shortest incubation time tested (5 minutes), a 99.9% reduction in viruses in the buffer has been observed, indicating that polyester / cotton and cellulose materials have a rapid effect on viruses-a key core feature of the function of mask materials, and indicate that they have a high efficacy in isolating viruses.

[0269] refer to Fig.12, the virus filtration efficacy test is adapted from ASTM F2101, US FDA Good Manufacturing Practice (GMP) regulations 21CFR Parts 210, 211 and 820. The virus filtration efficiency (VFE) of the test article is determined by comparing the virus control counts upstream of the textile substrate (e.g., 2%-9% BPEI spunlace or C-POLAR spunlace containing nonwoven fibers) treated with a space charge electret material with the counts downstream. Five test items were tested by Nelson Laboratories, while the other five test items were tested by the testing laboratory Intertek. Briefly, a suspension of bacteriophage φX174 was atomized using an atomizer and delivered to the textile substrate material treated with a space charge electret material at a constant flow rate and fixed air pressure. The challenging delivery was maintained at 1100–3300 plaque forming units (PFU) with an average particle size (MPS) of 3.0±0.3μm. The test area was approximately 40cm 2 The VFE flow rate was 28.3 liters / minute (L / min), at 85±5% relative humidity and 21±5°C, with a minimum duration of 4 hours. The average value of the positive control was 1.6X 10 3 PFU, negative monitoring counts are <1 PFU. Aerosol droplets were drawn through a six-stage active particle Anderson sampler for collection. The results show that textile substrates treated with space charge electret materials can effectively prevent viruses from penetrating textile filters. Cellulose / polyester textiles treated with BPEI space charge electret materials have been shown to have a virus filtration efficacy of more than 99.9%. No plaques were detected on any of the Andersen sampler plates.

[0270] Antibacterial effect

[0271] refer to Fig.13 and Fig.14 The antimicrobial activity of textile substrates (2%-9% BPEI spunlace fabrics) treated with space charge electret materials was tested. Briefly, the textile substrates treated with space charge electret materials were washed 60 times in a washing machine with cold water and washing powder. 1 ml of 1x 10 6 CFU / ml to 3x 10 6CFU / ml of Staphylococcus aureus inoculum, wherein each textile substrate treated with space charge electret material is placed on an agar surface and loaded with a 200g stainless steel cylinder for 60 seconds ± 5 seconds to transfer the microbial content. The bacterial colony count is measured according to the plate count method specified in Annex C of BS EN ISO 20743:2013. The test results of killing Staphylococcus aureus by different textile substrates treated with BPEI space charge electret material without washing, before washing and after washing 60 times are summarized. According to the method of Wiegand C., Heinze T. and Hipler UC (2009), Comparative in vitro study on cytotoxicity, antimicrobial activity, and binding capacity for pathophysiological factors in chronic wounds of alginate and silver-containing alginate. Wound Repair Regen., 17, 511-521, an antimicrobial activity value of less than 0.5 is determined to represent no antimicrobial activity. Values ​​between 0.5 and 1 were rated as slight activity, values ​​greater than 1 and less than or equal to 3 were rated as significant activity, and a log reduction greater than 3 represented strong antibacterial activity.

[0272] Table 2. Fig.13 The material of the textile substrate in each sample number.

[0273] Fig.13 The sample numbers shown in Materials for textile substrates Space Charge Electret Materials #1 50% cotton / 50% polyester 2%-9% BPEI #2 50% cotton / 50% polyester 2% -9% BPEI

[0274] Table 3. Fig.14 The material of the textile substrate in each sample number.

[0275]

[0276]

[0277] Taken together, the results show that both 50% cotton / 50% polyester and 35% cellulose / 65% polyester textiles treated with BPEI space charge electret materials killed Staphylococcus aureus with over 99.9% efficacy. The antimicrobial activity values ​​of the textile substrates after 60 washes were all greater than 3, indicating that 60 washes had little effect on the strong antimicrobial activity of the BPEI treated cellulose / polyester textile materials.

[0278] refer to Fig.15, the effectiveness of filters treated with space charge electret materials in preventing bacteria from penetrating the filter during rapid airflow was evaluated. The bacterial filtration efficiency test was adapted from ASTM F2101:2019. The bacterial filtration efficiency (BFE) of the test article was determined by comparing the bacterial control counts upstream of a textile substrate (2%-9% BPEI spunlace fabric containing 50% cotton / 50% polyester) treated with a space charge electret material with the counts downstream. Briefly, a suspension of Staphylococcus aureus in peptone water was atomized using an atomizer and delivered to a textile substrate treated with a space charge electret material at a constant flow rate and fixed air pressure at 21±5°C and 65±5% relative humidity for a minimum of 4 hours. The challenging delivery was maintained at 2200 colony forming units (CFU) with a mean particle size (MPS) of 3.0±0.3 μm. The aerosol droplets were drawn through a tryptic soy agar plate under vacuum for collection (flow rate: 100 liters per minute). After incubation at 37±2°C for 48±4 hours, the number of Staphylococcus aureus colonies formed on the tryptic soy agar plates was counted. The results showed that the 50% cotton / 50% polyester textile treated with the BPEI space charge electret material achieved a bacterial filtration efficacy of more than 99.9%. No bacterial colonies of Staphylococcus aureus were detected. These results confirm that the cotton / polyester textile treated with the BPEI space charge electret material prevented all bacteria from penetrating the filter when a fast airflow was used.

[0279] Cytotoxicity

[0280] refer to Fig.16 and Fig.17 The effects of BPEI space charge electret material (C-POLAR) on cellulose textiles and cellulose / polyester textiles treated with different solution concentrations on the viability of VERO E6 cells were studied. Briefly, 1 x 1 cm2 of cellulose textiles treated with 4%, 6%, or 8% BPEI space charge electret material (C-POLAR) were placed on the cellulose / polyester textiles. 2 The textile substrate was incubated in 10 ml of DMEM complete medium for 30 minutes. After incubation, the culture medium was transferred to VERO E6 cells in 96-well plates in triplicate at 10-fold dilutions and incubated for 72 hours at 37°C, 5% CO2. Cell viability was determined by adding XTT solution for 4 hours and measuring the absorbance of the newly formed orange formazan solution using an EnVision plate reader. The absorbance was normalized to the no sample control set to 100% and compared to log in GraphPad software 10The dilutions were plotted. The results showed that washout from the control textile and the space charge electret material treated textile moderately reduced the proliferation of VERO E6 cells. For 3 days of incubation, there was no difference in VERO E6 cell proliferation between the untreated and C-polar treated textiles.

[0281] refer to Fig.18 , studied the cytotoxicity of different concentrations of BPEI space charge electret material (C-POLAR) to GMK (green monkey kidney) cells and MRC5 (Medical Research Council cell line 5, derived from human lung tissue) cells. The liquid preparation of BPEI space charge electret material was diluted to 8%, 4%, 2%, 1%, 0.5%, 0.25%, 0.124%, etc. using cell culture medium. The diluted BPEI space charge electret material was transferred to a culture plate, and then an equal volume of cells suspended in complete culture medium was added to each well, and repeated in 8 parallel wells in a 96-well plate. The cells were incubated at 37°C for 5 days until the bottom of the plate in each well was covered with cells. At the end of the 5th day, the cells were fixed and stained to visualize the cells that survived and replicated. The results showed that for 5 days of incubation, 0.5% of the BPEI space charge electret material remained comparable to the control. It was also shown that if 8.3% of the total polymer on the textile substrate treated with the BPEI space charge electret material was abraded away, no significant cytotoxicity towards GMK cells and MRC5 cells occurred.

[0282] refer to Fig.19 and Fig. 20 , studied the effect of BPEI space charge electret material treatment on cell sensitivity of cellulose textiles and cellulose / polyester. Briefly, 1 x 1 cm treated with 4%, 6%, or 8% BPEI space charge electret material 2 The textile substrate was washed in 10 ml of DMEM complete medium by vortexing 5 times for 5 seconds each time. 5 ml of the medium was transferred to another tube, 50 μl of SARS-CoV-2 (100,000 IU / mL) was added, and the mixture was incubated at room temperature for 30 minutes. After incubation, 200 μl of the mixture was taken out and titrated by plaque assay in a 24-well plate in DMEM complete medium using a 10-fold dilution. The virus was gently mixed with the cells (250 000 / well) and incubated at 37°C for 4 hours. Afterwards, 0.4 ml of 3% carboxymethyl cellulose was added and the plates were incubated for 5 days. After incubation, the cells were washed, stained with naphthol blue-black dye, washed with water and dried. Plaques were counted in pfu / ml and expressed as log 10 Compared with the untreated control, log 10 pfu / ml comparison to determine the log of viral titer 10The results showed that no decrease in cell sensitivity was found.

[0283] refer to Figures 21A-21C The textile substrates treated with 2%-9% BPEI space charge electret materials were tested according to ISO 10993-5 (in vitro cytotoxicity test), ISO 10993-10 (animal skin irritation test) and ISO 10993-10 (skin sensitization test) to determine the biocompatibility of the treated textile substrates. For the in vitro cytotoxicity test, the treated textile substrates were sterilized at 121°C for 30 minutes and incubated with 1640 medium at 3 cm 2 / ml ratio at 37 ° C for 24 hours. The positive control was a polyurethane membrane containing 0.1% zinc diethyldithiocarbamate (ZDEC). Mouse fibroblasts L929 were cultured in RPMI 1640 medium supplemented with L-glutamine, 10% FBS and penicillin-streptomycin at 37 ° C and 5.0% CO2. L929 cells were seeded in a 96-well plate and 100 μl of cell solution was added to each well at a density of 1x 10 5 cells / ml. L929 cells were treated with the extraction medium of the treated textile substrates and 6 replicate wells were used. After 24 hours of treatment, 50 μl of MTT solution was added to each well. After incubation, washing and isopropanol extraction, the absorbance of each well was measured at 570 nm using a spectrophotometer and the cell viability was calculated. Fig.21A The results in show that the cytotoxicity of the textile substrate treated with the BPEI space charge electret material was level 0, which is considered to be non-cytotoxic.

[0284] Four healthy female New Zealand white rabbits were used for the skin irritation test. The rabbits were kept at room temperature (18-23°C) and relative humidity of 45-65%. Fig. 21B The results in showed that textile substrates treated with 2%-9% BPEI space charge electret materials were found to be negligibly irritating to rabbit skin based on the major irritation index category in rabbits.

[0285] For the skin sensitization test, female guinea pigs, 300-500 g each, were used. The guinea pigs were kept at room temperature (20-22° C.) and relative humidity of 45-65%. Fig. 21C The results in show that the textile substrate treated with BPEI space charge electret material does not cause delayed skin contact sensitization in guinea pigs. Taken together, it is revealed that the textile substrate treated with BPEI space charge electret material is a biocompatible material.

[0286] Method for loading space charge electret material on textile substrate

[0287] refer to Fig. 22 , which shows a method for loading a space charge electret material on the surface of a textile substrate. The textile substrate is formed into a dry web by combing. As an exemplary embodiment, the textile substrate can be natural cotton, wool, cellulose, synthetic polyester, nylon and / or their blends. The space charge electret material is loaded onto the fabric surface of the dry web by a high-pressure liquid flow to form a nonwoven fabric. A special online treatment is performed. Then, by drying and winding at high temperature, the space charge electret material forms a crosslinking agent with the fabric surface to form the surface of the textile substrate.

[0288] refer to Fig.23 , a flow chart for designing and manufacturing biocompatible space charge electret materials with high charge density for antibacterial, antiviral, bactericidal and virucidal applications based on cationic polymers and textile substrates is given. One or more types of cationic polymers with different positive charge densities and surface wettability (hydrophilicity and / or hydrophobicity) can be selected to design and manufacture high charge density space charge electret materials with suitable hydrophobicity to meet the specific requirements of the target application. The hydrophilicity of the space charge electret material can be adjusted by the type and density of the cation-bearing group, while the hydrophobicity can be adjusted by the length of the hydrophobic alkyl chain and the hydrophobic group. They can be dissolved in their appropriate solvents to prepare uniform dispersions to modify textile substrates by a combination of dipping / spraying and drying. In order to achieve good antibacterial, antiviral, bactericidal and virucidal effects, the positive charge density of the space charge electret material should be at least 9.59 nC cm -2 In preferred embodiments, the positive charge density of the space charge electret material is uniform or substantially uniform (constant) over the entire surface area of ​​the electret material. In some embodiments, the textile substrate is composed of hydrophobic fibers. In order to achieve biocompatible properties, the composition (e.g., components and component ratios) should be controlled to be non-toxic.

[0289] Method for preparing bonding composition

[0290] Figures 24A-24BA method for preparing a joint composition of the present disclosure is illustrated, wherein a linear or branched PEI is hydrogen bonded to a fiber substrate (an example of a hydrophobic material). Such hydrogen bonding is achieved as follows: a certain amount of linear or branched PEI is first dissolved in water at 20°C to form a 6 wt% PEI aqueous solution. The fiber substrate is then dipped into the resulting PEI solution and / or the resulting solution is sprayed onto the fiber substrate. In some preferred embodiments, the fiber substrate is immersed in the PEI solution for 2-10 seconds. Finally, the immersed fiber substrate is air dried, optionally heated, preferably heated at a temperature of 50°C-160°C for at least 5 seconds, and / or optionally subjected to a tensioning process, which may include stretching, steaming, heating, pressing and / or subjecting the coated fiber substrate to one or more actions of pressure (including high airflow pressure or mechanical pressure). The resulting PEI-coated fiber substrate is confirmed by measuring the change in gram weight (grams per square meter), where a limited tolerance for change is considered acceptable.

[0291] In the most preferred embodiment of the present invention, a tensioning process is applied to the coated fiber substrate material, wherein the "tensioning process" includes one or more actions of stretching, steaming, heating, pressing, or subjecting the material to pressure (including high airflow pressure or mechanical pressure). For example, the fiber substrate material can be pulled into a heating chamber with rollers and dried at a higher temperature (e.g., 160°C). It should be understood that the force applied to the textile substrate material can be adjusted by the rollers. In addition, the drying time and temperature can also be adjusted. In some exemplary embodiments, the temperature is 100°C-200°C, 150°C-200°C, 150°C-175°C, 175°C-200°C, 150°C-170°C, or 155°C-165°C. In the most preferred embodiment, the temperature is 160°C.

[0292] The resulting PEI coated fiber substrate material can be confirmed by measuring the change in grammage (grams per square meter), with a 10% change being considered acceptable.

[0293] The mass change of the PEI modified textile can be calculated by W = (m1-m0 / m0*100%), where m1 is the gram weight of the PEI modified textile substrate material, and m0 is the gram weight of the original textile substrate material.

[0294] Branched PEI : Selected Exemplary Embodiment 1

[0295] In an exemplary embodiment, 60g of branched PEI polymer (MW 20000) is dissolved in 940ml of water at room temperature and stirred for at least 5 minutes to form a 6% branched PEI solution. A 0.30mm thick 50% polyester 50% cotton cellulose fabric material is immersed in the 6% branched PEI solution for 2-10 seconds, or the fabric material is sprayed with a spray method in a spray chamber. Once fully wetted, the fabric material is subjected to a tensioning process, wherein the PEI coated fabric is pulled into a heating chamber with rollers and dried at 160°C for at least 5-20 seconds. "Tensioning" may also include one or more actions of stretching, steaming, heating, pressing and / or subjecting the material to pressure (including high airflow pressure or mechanical pressure). The resulting coated fabric material is characterized by gram weight measurement and FT-IR attenuated total reflectance (ATR) spectroscopy. The antimicrobial properties can be confirmed via the tests described herein.

[0296] Branched PEI : Selected Exemplary Embodiments II

[0297] In another exemplary embodiment, 40 g of branched PEI polymer (MW 25000) was dissolved in 960 ml of water at room temperature and stirred for at least 5 minutes to form a 6% branched PEI solution. A 0.30 mm thick 50% polyester / 50% cotton cellulose fabric material was immersed in the 6% branched PEI solution and then dried at 160° C. for 10 seconds. The resulting coated fabric material was characterized by gram weight measurement and FT-IR attenuated total reflectance (ATR) spectroscopy.

[0298] The weight of the original 50% polyester / 50% cotton cellulose fabric material is 35-75g / m 2 The BPEI modified 50% polyester / 50% cotton cellulose fabric material treated with 1%-6% of the BPEI solution according to the embodiments disclosed above had a mass change W between 10% and 70%.

[0299] Linear PEI : Selected Exemplary Embodiments

[0300] In another preferred embodiment, 500 mg of linear PEI polymer is dissolved in 500 ml of water to form a uniform and clear solution. A 0.30 mm thick 50% polyester / 50% cotton cellulose fabric material is used as a substrate and soaked in the linear PEI solution for 5 minutes, then taken out for air drying. In the most preferred embodiment, when the wet substrate no longer drips under gravity, it is transferred to an oven at 60°C for accelerated drying. The dried substrate is double-sided ironed at 160°C. Finally, it is dried at 60°C to obtain a linear PEI-modified 50% polyester / 50% cotton cellulose fabric material. The resulting coated fabric is characterized by gram weight measurement and FT-IR attenuated total reflection (ATR) spectroscopy.

[0301] The antimicrobial properties of PEI and BPEI modified fabrics can be confirmed via the tests described herein.

[0302] Method for preparing Si-joint composition

[0303] Figures 25A-25B Illustrated is a method in which a silyl linker having an epoxy group is first bonded to a fiber substrate (hydrophobic material) and to each other via a single -O-linker; and then combined with a linear or branched PEI via an epoxide ring-opening reaction.

[0304] In an exemplary embodiment, 10 g of 3-glycidyloxypropyltrimethoxysilane ( Fig.25A (i)) was dissolved in 1000 mL of acetic acid / water solution at room temperature. The pH of the aqueous solution was adjusted to 5.3 by adding acetic acid. The methoxy group reacted with water via hydrolysis to form Fig.25A(ii) of a 1% silane aqueous solution of the compound. A fiber substrate, such as a 0.30 mm thick 50% polyester 50% cellulose material, is then soaked in a 1% silane aqueous solution. The solution is heated to 40°C and maintained for 2 hours to obtain a compound of formula 25A(iii), wherein at least some of the silyl linkers are bonded to each other via a single -O-linker. The reaction also results in the compound of formula 25A(iii) being bonded to the fiber substrate via an -O-linker to form a compound of formula 25A(iv). The modified fiber substrate 25A(iv) is removed from the solution to "drain water in the air", which means removing a portion of the excess water by physical means, such as draining in the air or gravity dripping. In the most preferred embodiment, the modified fiber substrate 25A(iv) is then transferred to an oven for further heating and drying at 60°C for 2 hours. After the water is completely removed (i.e., the modified fiber substrate 25A(iv) is completely dried), the dried modified fiber substrate 25A(iv) is further washed with pure water to remove any remaining starting materials, unreacted compounds and acetic acid. The washed modified fiber substrate 25A(iv) was redried at 60°C for 2 hours. After drying, the modified fiber substrate 25A(iv) was immersed in a linear PEI solution doped with lithium perchlorate and further tensioned at 160°C for at least 10 seconds, so that the PEI polymer and the linker were bonded via epoxide ring-opening to form a compound of formula 25A(v). The linear PEI modified fiber substrate of formula 25(A)(v) was transferred to an oven and heated at 60°C for 2 hours. Finally, the compound of formula 25(A)(v) was washed with pure water to remove unreacted or unbonded polymer and catalyst, and redried at 60°C for 2 hours. The branched PEI was also chemically bonded to the fiber substrate by the same procedure, as Fig.25B as shown in .

[0305] Fig.26AThe method steps for bonding the cationic polymers of the present disclosure to the textile / fiber substrate are illustrated. First, a cationic polymer solution is prepared by dissolving one or more cationic polymers in a suitable solvent. Next, the cationic polymer solution is applied to the textile / fiber substrate by dripping, spraying, dipping or other methods known to those skilled in the art. In a selected preferred embodiment, the substrate is coated with the cationic polymer in a manner that makes the coating and the resulting positive charge density uniform or substantially uniform over the entire surface area of ​​the textile / fiber substrate. Next, the textile / fiber substrate coated with the one or more cationic polymers is subjected to tensioning. "Tensioning" includes one or more of stretching, steaming, heating, pressing and subjecting to pressure (including high air flow pressure or mechanical pressure), during and / or after which the one or more cationic polymers are hydrolyzed and then dehydrated, wherein some silyl-hydroxyl groups may optionally condense with each other. For example, cationic polymers with silyl joints are bonded to each other via a single -O-joint. Afterwards, the dehydrated / condensed cationic polymer forms hydrogen bonds with the textile / fiber substrate, followed by chemical bonding between the dehydrated / condensed cationic polymer and the hydroxyl groups of the textile / fiber substrate. After tensioning, the mixture is washed to remove unbound components and then dried to obtain a textile / fiber substrate with a cationic polymer.

[0306] Fig.26B An example schematic diagram showing how a branched cationic polymer is bonded to a fiber substrate. A branched cationic polymer 26B (i) having (one or more) silyl joints is dissolved in water under hydrolysis conditions to form a branched cationic polymer 26B (ii) solution having (one or more) silyl joints. The fiber substrate is then soaked in a 6% solution of a branched cationic polymer 26B (ii) having (one or more) silyl joints at 40° C. for 2 hours to first form a branched PEI-connected fiber substrate 26B (iii) and then form an antimicrobial composition of formula 26B (iv). The modified fiber substrate containing a mixture of compounds of formula 26B (iii) and formula 26B (iv) is removed from the solution, drained in air, and then transferred to an oven and heated at 60° C. for 2 hours to form a compound of formula 26B (iv). After complete drying, the modified fiber substrate of formula 26B(iv) is washed with pure water to remove excess or unreacted compounds and redried at 60°C for 2 hours to obtain a surface-modified textile / fiber substrate with branched PEI, i.e., the antimicrobial composition of formula 26B(iv).

[0307] In an exemplary embodiment, 20 g of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane is dissolved in 1000 mL of aqueous solution at room temperature to form a 2% silane solution. A fiber substrate such as a 0.30 mm thick 50% polyester 50% cellulose material is then soaked in a 2% silane aqueous solution. The solution is heated to 40°C and kept for 2 hours. During this soaking process, the methoxy groups of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane react with water to form silanol groups via hydrolysis. It is chemically bonded to the fiber surface via a dehydration / condensation reaction with the hydroxyl groups of the fiber. 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane can also be first self-polymerized into an oligomer structure through a silanol self-condensation reaction and then grafted onto the fiber surface via an -O-joint. The modified fiber substrate is removed from the solution, drained in air, and transferred to an oven at 60°C for 2 hours. After complete drying, it was washed with pure water to remove the unattached compounds and re-dried at 60 °C for 2 h to obtain the surface-modified textile / fiber substrates with linear PEI molecules and oligomers.

[0308] Figures 27A-27B Shown are exemplary synthetic routes for preparing various silylated linear or branched PEI compounds via silylation reactions between chloroalkoxysilanes and PEI polymers (exemplary cationic polymers).

[0309] In an exemplary embodiment, 500 mg of a linear PEI polymer is dissolved in 200 mL of ethanol in a sealed container. The container is placed in an ice bath (0° C.) and nitrogen is bubbled into the solution to remove oxygen. Then 5 g of chlorotriethoxysilane is slowly dripped into the solution over 30 minutes at 0° C. in an atmosphere filled with N2, and stirred continuously for 1 hour, followed by stirring at 40° C. for 2 hours. The solution is then poured into an excess of ether to obtain a precipitate of a silylated linear PEI polymer, which is collected by filtration and further dried in a vacuum.

[0310] In another exemplary embodiment, 10g of branched PEI polymer is dissolved in 500mL of ethanol in a sealed container. The container is placed in an ice bath (0°C) and nitrogen is bubbled into the solution to remove oxygen. Then at 0°C in an atmosphere full of N2, 20g of chlorotriethoxysilane is slowly dripped into the solution over 30 minutes, and stirred continuously for 1 hour, then stirred at 40°C for 2 hours. Then 500mL of ether is poured into the solution to allow the liquid to be layered. A separating funnel is used to obtain a liquid layer of the branched PEI polymer containing silylation. The final product is further dried in a vacuum and sealed storage unit.

[0311] Figures 27C-27DThe example synthetic route of making silylated linear or branched PEI react with fiber substrate (hydrophobic material) is shown. In an example embodiment, 100mg of silylated linear PEI polymer is dissolved in 100mL ethanol / water (50 / 50, w / w) mixture at room temperature to form Si-PEI solution. Then the fiber substrate such as 0.30mm thick 50% polyester 50% cellulose material is immersed in Si-PEI solution for 30 minutes at room temperature, then heated to 40°C and kept for 2 hours. During this soaking process, the methoxyl groups of silylated linear PEI polymer react with water to form silanol groups via hydrolysis. The silanol groups are chemically bonded to the fiber surface via dehydration / condensation reaction with at least one hydroxyl group of the fiber substrate to form a modified fiber substrate. Take out the modified fiber substrate, drain the water in the air, and transfer to an oven at 60°C for 2 hours. After complete drying, it was washed with pure water to remove excess or unreacted compounds and redried at 60°C for 2 hours to obtain a surface-modified textile / fiber substrate with a silylated linear PEI polymer (Formula 27C (iii)), which has a chemical bonding between the silyl groups of the silylated linear PEI polymer and the hydroxyl groups of the fiber substrate.

[0312] In another exemplary embodiment, 6g of silylated branched PEI polymer is dissolved in 100mL ethanol / water (50 / 50, w / w) mixture at room temperature. Then the fiber substrate, such as 0.30mm thick 50% polyester 50% cellulose material, is immersed in the solution as prepared for 30 minutes. The solution temperature is further raised to 40°C and maintained for 2 hours. During this soaking process, the methoxy group reacts with water via hydrolysis to form a silanol group. It is chemically bonded to the fiber surface via a dehydration / condensation reaction with the hydroxyl group of the fiber. Take out the modified fiber substrate, drain the water in the air, and transfer to an oven at 60°C for 2 hours. After complete drying, wash with pure water to remove unattached compounds, and re-dry at 60°C for 2 hours to obtain a surface-modified textile / fiber substrate (Formula 27D (iii)) with a silylated branched PEI polymer, which has a chemical bonding between the silyl group of the silylated branched PEI polymer and the hydroxyl group of the fiber substrate.

[0313] Methods for designing and making novel antimicrobial compositions

[0314] This paper provides a novel disinfection mechanism of space charge electret materials to capture and kill microorganisms (such as bacteria and viruses) through the synergistic effects of contact electrification, non-contact electrostatic interaction and interfacial lipophilicity, so as to guide the design and manufacture of biocompatible space charge electret materials with excellent antibacterial, antiviral, bactericidal and virucidal effects based on biocompatible cationic polymers and textile substrates. Space charge electret materials should have both high positive charge density and appropriate hydrophobicity to achieve excellent antibacterial, antiviral, bactericidal and virucidal effects. The positive charge density plays a key role in the degree of antibacterial and antiviral activity of space charge electret materials.

[0315] First, the space charge electret material with high positive charge density attracts biohazards (such as bacteria and viruses) with negatively charged proteins via non-contact electrostatic interactions, resulting in an increase in collision rate. Then contact electrification occurs when the drifting negatively charged biohazard collides with the positively charged electret, resulting in a sharp change in electrostatic potential and a sudden increase in electrical stress. The strong electrostatic field tightly fixes or traps the biohazard on the positively charged surface, and the generated non-uniform electrical stress helps to cut or tear off the envelope protein and / or other key viral or microbial proteins of the biohazard. In the close contact process, the hydrophobicity of the space charge electret material helps its lipophilic partition to be inserted into the biohazard film via van der Waals interactions, thereby helping to destroy the biohazard more easily and quickly. By correctly selecting a textile substrate with a suitable structure, a space charge electret material based on a cationic polymer and a textile substrate can have a high virus and bacteria filtration effect. Such space charge electret materials can be widely used in air filtration products (such as masks, protective clothing, air filters and air purifiers) and personal / household hygiene products (such as hand disinfectants, wet wipes and toilet paper), home / hotel textiles and related disposable hygiene products.

[0316] Specific exemplary embodiments - Group 1

[0317] This paper provides a novel disinfection mechanism in which space charge electret materials capture and kill microorganisms (such as bacteria and viruses) through the synergistic effects of contact electrification, non-contact electrostatic interaction, and interfacial lipophilicity, to guide the design and manufacture of biocompatible space charge electret materials with excellent antibacterial, antiviral, bactericidal, and virucidal effects based on biocompatible cationic polymers and textile substrates.

[0318] The positive charge density plays a key role in the degree of antibacterial and antiviral activity of space charge electret materials.

[0319] First, space charge electret materials with high positive charge density attract target biohazards (such as bacteria and viruses) with negatively charged proteins via non-contact electrostatic interactions, resulting in an increase in the collision rate.

[0320] Then, when the drifting negatively charged biohazard collides with the positively charged electret, contact electrification occurs, resulting in a sharp change in electrostatic potential and a sudden increase in electrical stress. The strong electrostatic field causes the biohazard to become tightly fixed on the positively charged surface, and the generated non-uniform electrical stress helps to tear off or shear the envelope protein and / or other key viral or microbial proteins of the target biohazard.

[0321] During close contact, the hydrophobicity of the space charge electret material helps its lipophilic partition to insert into the biohazard membrane via van der Waals interactions, thereby facilitating easier and faster destruction of the biohazard.

[0322] This article provides a technical route for preparing a space charge electret material with high charge density and suitable surface hydrophobicity using one or more types of cationic polymers and a hydrophilic fiber / hydrophobic blended textile substrate;

[0323] This paper provides a new application of using space-charge electret materials to achieve biocompatible disinfectants / sanitizers with excellent antibacterial, antiviral, bactericidal, and virucidal effects;

[0324] This paper provides a new application of using space charge electret materials to achieve air filters with high virus filtration efficiency and bacteria filtration efficiency;

[0325] In order to achieve excellent antibacterial, antiviral, bactericidal and virucidal effects and high virus / bacteria filtration efficiency, the positive charge density of textile substrates treated with cationic polymers exceeds 9.59 nC cm -2 In some embodiments, the textile substrate is composed of hydrophilic fibers (such as cellulose) and hydrophobic fibers (such as polyester).

[0326] This article provides a method and apparatus for evaluating contact electrification of space charge electret materials.

[0327] This paper provides a positive charge density parameter for quantitatively evaluating the degree of contact electrification.

[0328] This paper provides a device for measuring the positive charge of space charge electret materials, which is based on a bottom acrylic plate mainly composed of a 6cm×6cm bonded electrode layer fixed to it and an upper acrylic plate fixed to a reference material / electrode layer of the same size. A PTFE membrane is fixed as a reference material. The test samples can be woven / knitted / non-woven fabric samples and membranes.

[0329] During the test, the sample (such as a nonwoven textile substrate modified with a space charge electret material surface) is flatly and tightly adhered to the adhesive electrode on the bottom acrylic plate. The upper acrylic plate can be controlled by a machine to repeatedly contact / impact the bottom acrylic plate. This allows contact between the surface of the space charge electret and the surface of the material modified textile (modified with PTFE) under external pressure and allows them to separate after the external pressure is released.

[0330] An electrometer was connected to the electrodes to monitor and measure the charge changes in real time, and the stable charge curve generated and measured during repeated contact and separation was recorded for further analysis.

[0331] Typically, the maximum charge value occurs during the contact state, and the minimum charge value occurs during the separation state. The difference in charge value during the contact and separation states can be determined as the positive charge generated by contact electrification. The positive charge density is calculated by dividing the positive charge by the effective contact area (e.g., 6 cm x 6 cm) to quantitatively evaluate the degree of contact electrification.

[0332] Although various embodiments of the present invention have been described, it will be apparent to those skilled in the art that many more embodiments and implementations are possible within the scope of the present invention. In addition, the various features, elements and embodiments described herein may be claimed or combined in any combination or arrangement.

Claims

1. An antiviral material, comprising: A cationic polymer space charge electret material having antiviral properties bonded to a hydrophobic substrate material, wherein the cationic polymer is natural, semisynthetic or synthetic; Furthermore, wherein the cationic polymer has a linear, branched, hyperbranched or dendrimer-like structure and the cationic polymer comprises at least a cation-bearing group located in the main chain or a side chain of the cationic polymer; and The hydrophobic material has a surface that is positively charged in a uniform manner.

2. The antiviral material according to claim 1, wherein the cationic polymer is selected from PEI, linear polyethyleneimine, branched polyethyleneimine, gelatin, chitosan, cationic peptides, cationic cyclodextrin, cationic dextran, cationic cellulose, polylysine, polyamidoamine, poly(amino-co-ester) or poly[2-(N,N-dimethylamino)ethyl methacrylate], polyethyleneimine.

3. The antiviral material according to claim 2, wherein the cationic polymer is polyethyleneimine.

4. The antiviral material according to claim 3, wherein the space charge electret material comprises 0.195% to 10% of polyethyleneimine cationic polymer.

5. The antiviral material of claim 4, wherein the space charge electret material comprises substantially 2% to 8% of polyethyleneimine cationic polymer.

6. The hydrophobic material of claim 1, wherein the hydrophobic substrate material is one or more of the following: cotton-polyester blends, cotton, polyester, cellulose-polyester blends, cellulose, spunlace, polypropylene (PP), polylactic acid (PLA), polyethylene (PE), polyvinyl chloride (PVC), acrylonitrile butadiene styrene (ABS), poly(methyl methacrylate) (PMMA), polytetrafluoroethylene (PTFE), silicone, latex, nylon or glass.

7. The hydrophobic material according to claim 5, wherein the hydrophobic substrate material is one or more of the following: cotton-polyester blend, cotton, polyester, cellulose, polypropylene, polyethylene or spunlace.

8. The antiviral material according to claim 1, wherein the material has a relative humidity of 2-35 nC cm -2 The minimum average positive surface charge.

9. The antiviral material of claim 1, wherein the material retains antiviral efficacy after being woven, bonded, blended or mixed with other non-antiviral materials in a certain volume.

10. The antiviral material according to claim 1, wherein the material is formed into a porous sheet, a film, a woven fabric or a nonwoven fabric.

11. A method for producing an antiviral material, the method comprising: dissolving a space charge electret material in a suitable solvent to form a space charge electret material / solvent mixture, wherein the concentration of the space charge electret material in the solvent is 0.195% to 10%; applying the space charge electret material / solvent mixture to a hydrophobic substrate by dip coating and / or spray coating to coat the hydrophobic substrate material; The resulting coated hydrophobic material is subjected to a tensioning process, wherein the tensioning process includes one or more of steaming, heating, pressing, and / or subjecting to pressure; and washing the material to remove unbonded mixture components.

12. The method of claim 11, wherein the space charge electret material is dissolved in a solvent without added salt.

13. The method of claim 12, wherein the solvent is water.

14. The method of claim 11, wherein the space charge electret material is 0.195%-10% polyethyleneimine.

15. The method of claim 14, wherein the space charge electret material is substantially 2%-8% polyethyleneimine.

16. The method of claim 11, wherein the space charge electret material / solvent mixture is uniformly spread on the hydrophobic substrate material to form a polymer-impregnated substrate material, and further wherein the polymer-impregnated substrate is heated at 50-160 degrees Celsius for at least 5 seconds.

17. The method of claim 11, wherein the hydrophobic substrate material is one or more of the following: cotton-polyester blends, cotton, polyester, cellulose-polyester blends, cellulose, spunlace, polypropylene (PP), polylactic acid (PLA), polyethylene (PE), polyvinyl chloride (PVC), acrylonitrile butadiene styrene (ABS), poly(methyl methacrylate) (PMMA), polytetrafluoroethylene (PTFE), silicone, latex, nylon, or glass.

18. The method of claim 17, wherein the hydrophobic substrate material is one or more of the following: cotton-polyester blend, cotton, polyester, cellulose, or spunlace.

19. The method of claim 11, wherein the resulting coated hydrophobic material has a hydrophobicity of 2-35 nC cm -2 The minimum average positive surface charge.

20. The method of claim 11, wherein the material is formed into a porous sheet, a film, a woven fabric, or a nonwoven fabric.